1993
DOI: 10.1128/jcm.31.5.1232-1236.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific antigens of Pseudomonas pseudomallei and evaluation of their efficacies for diagnosis of melioidosis

Abstract: Current methods for the diagnosis of melioidosis are based on bacteriological culture. A number of serological tests currently available lack specificity and sensitivity. This is largely due to the use of crude antigens which results in a significant cross-reactivity with sera from individuals infected with other bacteria. In this study five different antigens were prepared and evaluated for their potential usefulness in diagnosis of melioidosis. These included a 19.5-kDa antigen which was previously shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…That is, probably, the reason why sensitivity of the IHA test in the septicaemic group of our patients was low (70%). The detection of IgM antibody was not tested by ELISA in this study; however, with a partially purified antigen, Anuntagool et al [3] found that the detection of IgG antibody by ELISA was more reliable than that of IgM antibody in acutephase sera. This conclusion was contrary to that of Ashdown [I 51.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…That is, probably, the reason why sensitivity of the IHA test in the septicaemic group of our patients was low (70%). The detection of IgM antibody was not tested by ELISA in this study; however, with a partially purified antigen, Anuntagool et al [3] found that the detection of IgG antibody by ELISA was more reliable than that of IgM antibody in acutephase sera. This conclusion was contrary to that of Ashdown [I 51.…”
Section: Discussionmentioning
confidence: 60%
“…A glycolipid spot can also be obtained on thinlayer chromatograms of the extractable lipids from B. cepacia and B. mallei (data not shown). The problem was the same: as that encountered with the 19.5kDa antigen [3], h.owever, the amount of glycolipid from B. mallei was too small to make its purification possible. The existence of GL in these two bacteria is not unexpected because B. pseudomallei and B. cepacia belonged to the same RNA homology group [ 131, DNA-DNA homology value between B. pseudomallei and B. mallei was more than 90% and the sequences of 1174 bases of 16s rRNA of the two species matched completely [ 141.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The more widely used serological methods for antibody detection are difficult to interpret, particularly in areas where the infection is endemic, where the background antibody levels may be elevated. This drawback still persists even when more-purified antigens are used for detection (2,5). The quantitation of specific IgM antibody, as carried out in several laboratories (6), is not completely satisfactory because false positives still occur.…”
mentioning
confidence: 99%